The Relationship Between Processed Food Consumption and Periodontal Disease: Sex Disparities in the Majorcan Adolescent Population - Irene Coll; Daniela Vallejos; Pablo Estebala; Nora López-Safont (Life)
Background: The diet of young people in Spain has changed significantly, with a departure from a balanced dietary pattern and a greater intake of processed foods. Such food generates an acidic environment in the mouth, which promotes the multiplication of bacteria capable of causing inflammation and damage to the gums. Aim: This study aimed to determine the association between the frequency of consuming processed foods and periodontal disease, as well as sex differences, in an adolescent population. Methods: A study was conducted on 233 students aged 15 to examine the frequency of food consumption and its correlation with periodontal disease. Differences were determined via a Student’s t-test to compare the means. A chi-square test was used to compare categorical variables. The 95% confidence interval estimate was used in all cases (p < 0.05). Results: It was observed that girls have a higher mean number of healthy sextants than boys (3.26 <semantics>±</semantics> 0.20 vs. 2.70 ± 0.21; p = 0.029). A statistically significant difference was noted between healthy and affected subjects in the frequency of consumption of packaged milkshakes (p = 0.003), industrial juices (p = 0.009), industrial pastries (p = 0.018), and fruits in syrup (p = 0.022). When segmented by sex, a statistically significant difference was noted in boys between healthy and affected subjects in the frequency of consumption of packaged milkshakes (p = 0.044), salty snacks (p = 0.032), and cold cuts (p = 0.033); in girls, the difference was detected in industrial juices (0.024). Conclusions: The results of this study suggest that adolescent boys are more affected periodontally than girls. In both sexes, the level of consumption of processed foods affects the presence of periodontal disease.